1983
DOI: 10.1113/expphysiol.1983.sp002731
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Transferrin and Transferrin Receptors in the Rabbit Placenta

Abstract: SUMMARYThe quantity and distribution of transferrin and transferrin-binding sites in the placenta were investigated in rabbits on the 28th-29th days of pregnancy. The animals were injected intravenously with a mixture of 59Fe-121I-labelled rabbit diferric transferrin and 131I-labelled rabbit albumin. The binding of transferrin to placentas removed 3-75 min later was determined by using the 13II-labelled albumin values to correct for tissue content of plasma. Mean values for transferrin binding of 1460 and 560 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Further, the inhibition of iron uptake by inhibitors of endocytosis is proportional to the inhibition of transferrin endocytosis [l SO] and both transferrin and its receptor are recycled to the cell surface by exocytosis [181] with a recycling time of 3-4 min at 37°C [160]. That receptor binding [182] and endocytosis [183] is also involved in transferrin and iron uptake by placenta is also well established.…”
Section: The Transferrin Cell Cyclementioning
confidence: 99%
“…Further, the inhibition of iron uptake by inhibitors of endocytosis is proportional to the inhibition of transferrin endocytosis [l SO] and both transferrin and its receptor are recycled to the cell surface by exocytosis [181] with a recycling time of 3-4 min at 37°C [160]. That receptor binding [182] and endocytosis [183] is also involved in transferrin and iron uptake by placenta is also well established.…”
Section: The Transferrin Cell Cyclementioning
confidence: 99%
“…Immunohistochemical studies have localized TFR1 and transferrin to the apical membrane of syncytiotrophoblasts. 25,26 Concordantly, immunoelectron microscopy demonstrated the presence of transferrin [26][27][28] and TFR1 29 on the membrane of cellular invaginations and intracellular vesicles, likely representing clathrin-coated endosomes that contain transferrin, 30,31 TFR1, 32 and TFR1-transferrin complexes. 30,32 Kinetic studies in BeWo cells 33 and placental microvillous membrane preparations 17,34,35 showed that diferric transferrin uptake is a specific and saturable process, with binding affinities similar to values reported in K562 erythroleukemia cells 36 and reticulocytes.…”
Section: Nonheme Iron Transport Iron Uptakementioning
confidence: 97%
“…We are not proposing that Fe is exclusively released via ' CO-Fe '. Indeed, apo-Tf and the ferroxidase caeruloplasmin may facilitate Fe release [178,179].…”
Section: The Co-fe Hypothesis Of Fe Mobilizationmentioning
confidence: 99%